2022
DOI: 10.1007/s10534-022-00458-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mimicry of the receptor-binding domain of the SARS-CoV-2 spike protein: from the interaction of spike-specific antibodies with transferrin and lactoferrin to the antiviral effects of human recombinant lactoferrin

Abstract: The pathogenesis of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection involves dysregulations of iron metabolism, and although the mechanism of this pathology is not yet fully understood, correction of iron metabolism pathways seems a promising pharmacological target. The previously observed effect of inhibiting SARS-CoV-2 infection by ferristatin II, an inducer of transferrin receptor 1 (TfR1) degradation, prompted the study of competition between Spike protein and TfR1 ligands, especiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 114 publications
1
4
0
Order By: Relevance
“…This finding is in line with a recent study showing that 1 mg/mL apo-or holo-hLf derived from the milk of transgenic goats promoted a similar pronounced reduction in the titers of SARS-CoV-2 ancestral and delta strains during infection of Vero E6 cells [30]. Since our data revealed that SARS-CoV-2 ancestral and omicron strains were also equivalent in terms of sensitivity to apo-or holo-bLf during infection, the ancestral one was selected for the next experiments as a precautionary measure due to its lower risk of community spread.…”
Section: Overall Antiviral Effect Of Apo-or Holo-blf On Sars-cov-2 In...supporting
confidence: 91%
“…This finding is in line with a recent study showing that 1 mg/mL apo-or holo-hLf derived from the milk of transgenic goats promoted a similar pronounced reduction in the titers of SARS-CoV-2 ancestral and delta strains during infection of Vero E6 cells [30]. Since our data revealed that SARS-CoV-2 ancestral and omicron strains were also equivalent in terms of sensitivity to apo-or holo-bLf during infection, the ancestral one was selected for the next experiments as a precautionary measure due to its lower risk of community spread.…”
Section: Overall Antiviral Effect Of Apo-or Holo-blf On Sars-cov-2 In...supporting
confidence: 91%
“…In addition, as Lf is reported to attach to the ACE2 cell receptor used by SARS-CoV-2 to enter the cell, the components of the liposome may induce protein changes in cellular TMPRSS2, which is also involved in the entry of this virus [15]. The mechanism of action of Lf against SARS-CoV-2 is also explained by its direct interaction with the receptor binding domain (RBD) of the Spike protein [30,31] and its binding to heparan sulfate proteoglycans, thus preventing the early attachment phase [14]. In addition, some in silico studies showed that Lf also interacts with the transferrin receptor 1, which can be an alternative co-receptor for SARS-CoV-2 entry [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Certain viruses have been found to hijack cellular TFR1 and promote virus internalization and by clathrin-mediated endocytosis. For example, TFR1 was shown to be a vital protein in promoting the entry of SARS-CoV-2 facilitating virus endocytosis (Sokolov et al, 2023). As a potential therapeutic target, TFR1 exhibits the effect of inhibiting SARS-CoV-2 infections by chemical inhibitors (such as ferristatin II) (Sokolov et al, 2022;.…”
Section: Ferroptosis and Viral Infections Iron Regulation And Viral I...mentioning
confidence: 99%